Culture and demography in organizations - Harrison, J. Richard (Book collections on Project MUSE., 2006)
How do corporations and other organizations maintain and transmit their cultures over time? Culture and Demography in Organizations offers the most reliable and comprehensive answer to this complex question to date. The first book on the subject to ground its analysis in mathematical tools and computer simulation, it goes beyond standard approaches, which focus on socialization within organizations, by explicitly considering the effects of demographic processes of entry, exit, and organizational growth. J. Richard Harrison and Glenn R. Carroll base their analysis on a formal model with three components: hiring, socialization, and employee turnover. In exploring the model's implications through computer simulation methods, the authors cover topics such as organizational growth and decline, top management teams, organizational influence networks, terrorist organizations, cultural integration following mergers, and organizational failure. For each topic, they identify the conditions influencing cultural transmission. In general, they find that demographic processes play a central role in influencing organizational culture and that studying these processes leads to some surprising insights unavailable when considering socialization alone. This book, which also serves as an ideal introduction to the increasingly popular use of computer simulation, will be an indispensable resource for scholars and students of organization theory and behavior, cultural studies, strategic management, sociology, economics, and social simulation.